Beginning Digital Image Processing Using Free Tools for Photographers - Montabone, Sebastian; Pohlmann, Frank; MacDonald, Brian; Andres, Clay.; Anglin, Steve; Beckner, Mark.; Buckingham, Ewan.; Cornell, Gary.; Gennick, Jonathan; Hassell, Jonathan; Lowman, Michelle; Moodie, Matthew; et al. (Berkeley, CA : Apress, 2009)
Since the advent of digital photography, we have been able to post-process our pictures. However, to do it properly, we have to become digital art apprentices. Sebastian Montabone is a computer vision expert who wants us to use our cameras and image processing software to come up with works of art. In this book, he teaches image processing techniques of ascending difficulty based on freely available tools. The book teaches you to use the best tools for the job, and it focuses on the techniques, not the environments or toolchains in which they run. Also in this book, you'll learn about the Canon Hack Development Kit (CHDK), which expands the features of some cameras.
Keywords: Computer science; Image processing; Computer Science; Computer Science, general; Image Processing and Computer Vision; Electronic books